Aspects of communication in the Romany minority - Toumová, Kristýna; Tóthová, Valérie (Jihočeská univerzita v Českých Budějovicích, Zdravotně sociální fakulta, 2019)
The goal of this study was to map communication in the Romany minority using the ‘model of culturally considerate and adjusted care’ by J. N. Giger and R. E. Davidhizar. The article is focused on verbal and nonverbal communication where we considered the opinion of the Romany population. Methods: We used the quantitative research method with a non-standardized questionnaire. There were 600 Romany respondents. The selection criteria were age, gender, place of residence and the Romany nationality. The questions were based on the ‘model of culturally considerate and adjusted care’ by J. N. Giger and R. E. Davidhizar. Results: The results show that using the Romany language in this minority is influenced by the way of life and place of residence of every person. It is a problem for them to understand information regarding nursing because they do not understand all the information provided by medical personnel. The Romany frequently use non-verbal communication, such as gestures (67.7%), facial expressions (44.5%), intensive eye contact (38.3%) or body postures (25.8%). Conclusion: The Romany minority seems like a very specific group due to their verbal and non-verbal expressions. These indicators distinguish them from the majority of society. Contemporarily, we can see a certain assimilation, mainly in the adoption of the language of the majority society. Due to integration, the original Romany language is disappearing because it is not passed on from generation to generation.
Aspekty komunikace u romské minority
Keywords: Communication; Giger and Davidhizar; Integration; Romany language; Romany minority; Romská minorita; komunikace; Giger a Davidhizar; romština; integrace